Rhythmic gymnastics intervention to reduce body mass index of school-age children with obesity and low physical activity - Anggraini, Nourmayansa Vidya; Ratnawati, Diah; Ritanti, Ritanti; Ramandhani, Defina (Intelektual Pustaka Media Utama, 2023)
Obesity is a widespread health concern, prevalent in both developed and developing countries. Among school-age children, obesity can lead to health problems and increase the risk of disability in adulthood. A sedentary lifestyle is a significant contributor to poor health and fitness, and consequently, it may elevate the risk of obesity. To address this issue, rhythmic gymnastics has emerged as a potential method for managing weight and reducing body mass index. The purpose of this study was to investigate the efficacy of rhythmic gymnastics intervention in reducing body mass index among school-age children with low physical activity levels. The intervention was carried out three times a week, and results after four weeks revealed that managed patients lost 1.7 kg of weight with a decrease in body mass index (BMI) of 0.60 SD, while resumed patients lost 2 kg with a decrease in BMI of 0.59. These findings indicate that rhythmic gymnastics intervention can be effective in reducing body mass index in school-age children.